2006
DOI: 10.1079/phn2005876
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a food-frequency questionnaire for use in pregnancy

Abstract: Objectives: As a part of an ongoing project to develop a nutritional screening tool, we evaluated the performance of a semi-quantitative food-frequency questionnaire (FFQ) in terms of validity in a Sheffield Caucasian pregnant population using two different statistical approaches -the correlation coefficient and the limits of agreement (LOA). The FFQ was designed specifically for pregnant women and previously used in a large-scale study. Design: A validation study. Setting: A community-based field study of a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
89
3
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(109 citation statements)
references
References 26 publications
(13 reference statements)
14
89
3
3
Order By: Relevance
“…For example, correlations of measured total energy intake in our obese group were r P 5 0?284/r S 5 0?334 and in our lean group were r P 5 0?462/r S 5 0?510; compared with previous reports of r S 5 0?27 (17) , r P 5 0?26 (28) , r P 5 0?24 (18) and r S 5 0?28 (19) in pregnant women (where r P is Pearson correlation, r S is Spearman correlation). The reasons for closer correlation in our lean women are unknown, but may reflect that this was a group of lean women who had consented to participate in a study of obesity in pregnancy, and so were well motivated and interested in health behaviour and weight in pregnancy.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…For example, correlations of measured total energy intake in our obese group were r P 5 0?284/r S 5 0?334 and in our lean group were r P 5 0?462/r S 5 0?510; compared with previous reports of r S 5 0?27 (17) , r P 5 0?26 (28) , r P 5 0?24 (18) and r S 5 0?28 (19) in pregnant women (where r P is Pearson correlation, r S is Spearman correlation). The reasons for closer correlation in our lean women are unknown, but may reflect that this was a group of lean women who had consented to participate in a study of obesity in pregnancy, and so were well motivated and interested in health behaviour and weight in pregnancy.…”
Section: Discussioncontrasting
confidence: 63%
“…Significant agreement was also seen for important nutrients such as Ca, Fe, vitamins E, B 6 , B 12 and C, and also for SFA, dietary cholesterol and sugars, in both our obese and lean groups, as observed by others (19) . However, correlations for energy-adjusted dietary fibre were poorer in the obese group (r P 5 0?044/r S 5 20?183) than the lean group (r P 5 0?377/r S 5 20?294), as well as other studies (r P 5 0?36-0?47 (28) and r P 5 0?56 (18) ). This suggests possible over-reporting of portion size/frequency of dietary fibre intake in the FFQ as opposed to underreporting in the FD; it has been reported that fruits and vegetables are perceived as healthy and are more likely to be over-reported in FFQ (29) .…”
Section: Discussionsupporting
confidence: 59%
“…the FFQ. Although validity of the information collected by FFQ has been shown by many validation studies (9,10) , this information is not as detailed as that collected by dietary records because it involves a recall bias (32) . It has been reported that the FFQ has a tendency of overestimate when there are many food items, and underestimate when there are few food items, compared with a dietary record (32) .…”
Section: Discussionmentioning
confidence: 99%
“…Isso é corroborado pelos gráficos de dispersão, que mostraram aumento na magnitude do viés à medida em que aumentou a ingestão. Essa característica também tem sido observada em outros estudos 26,39 . Esses resultados reforçam a necessidade de diferentes abordagens para testar a validade de um QFA 9,27 .…”
Section: Energia E Nutrientesunclassified